A PHENETIC ANALYSIS OF THE SPECIES OF IRANIAN OXYTROPIS (FABACEAE) BASED ON MORPHOLOGICAL DATA (Journal of Sciences, Islamic Republic of Iran)
A phenetic analysis is presented using SAHN clustering (UPGMA, simple matching coefficient). The resulting phenetic analysis is compared with the classification of Oxytropis as suggested by Bunge [2] and Vassilczenko [ll]. The results partly correspond with Bungean classification and suggest that there are basically four sections (Mesogaea, Oxytropis, Janthina, Eumorphu) which can be grouped under two subgenera, namely Oxytropis and Euoxytropis. The subgenus Oxyfropis including section Mesogaea and the subgenus Euoxytropis including sections Oxytropis, Janthina and Ortholema are upheld by this analysis. It is concluded that section Ortholema should be united with section Eumorphu or 0. masanderanensis, 0. Kuchunensis and 0. suavis moved to section Eumorpha. The results of cluster analyses were compared with the classification obtained by conventional methods and the relations among the taxa have been discussed